Examining Recovery Program Participants by Gender: Program Completion, Relapse, and Multidimensional Status 12 Months After Program Entry. (October 2020) - Logan, TK; Cole, Jennifer; Walker, Robert
This study examined individual-level characteristics and factors associated with program completion, relapse, and multidimensional status at follow-up for 213 men and 248 women who entered one of 17 peer-led recovery programs and who completed a follow-up interview 12 months later. Study results found that although there were some significant gender differences at program entry among participants entering Recovery Kentucky, there were few gender differences at follow-up. In addition, although participants had significant psychosocial problems, polysubstance use patterns, and severe substance use disorder (SUD), the majority of both men and women reported completing the program (80.3%), a small minority reported relapse (9.5%), and about one third had worse multidimensional status about 12 months after program entry. Lower quality of life rating at program entry was associated with program completion and with better multidimensional status at follow-up. Study results suggest the recovery program provides an important option for some of the most vulnerable individuals with SUD.